Testing of rotational exercise equipment to improve the vestibular system - Park, Y. S.; Kang, S. H.; Park, S. J.; Lim, Y. T. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The primary purpose of this study was to test the effect of training using the rotational exercise equipment developed in this study on the improvement of the vestibular system. In order to test the rotational exercise equipment developed in this study, 15 ordinary college students had trainings for 8 weeks and their nystagmus intensity was analyzed. The findings showed that the rotational training using the rotational exercise equipment affected vestibular balance, as it significantly decreased the slow phase velocity (SPV) immediately after rotational stimulation and reduced the recovery time of nystagmus to normal.